1987
DOI: 10.1002/jso.2930360409
|View full text |Cite
|
Sign up to set email alerts
|

Flow cytometric analysis for assessing the malignant potential of breast cancer

Abstract: Flow cytometric analysis was performed on 60 patients with breast cancer to investigate the relationship between DNA histogram and the malignant potential of breast cancer. DNA aneuploidy of breast cancer tended to increase with increasing stage and degree of nodal metastasis. The percent of cells in the S phase was significantly increased in the patients with metastasis compared to those without metastasis. Patients exhibiting percent S phase value of more than 20% showed a high frequency of metastasis even w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1990
1990
1992
1992

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Several other studies reveal a close correlation between aneuploid tumors and increasing histologic grade. 6,8,20,28,36 Other studies revealed no significant correlation between DNA content and histologic grade. 1,3,26 Previous studies on stage of breast carcinoma have yielded conflicting results.…”
Section: Discussionmentioning
confidence: 94%
“…Several other studies reveal a close correlation between aneuploid tumors and increasing histologic grade. 6,8,20,28,36 Other studies revealed no significant correlation between DNA content and histologic grade. 1,3,26 Previous studies on stage of breast carcinoma have yielded conflicting results.…”
Section: Discussionmentioning
confidence: 94%